Technological revolutions and the evolution of industrial structures: Assessing the impact of new technologies upon size, pattern of growth and boundaries of the firms - Giovanni Dosi; Alfonso Gambardella; Marco Grazzi; Luigi Orsenigo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2007)
In this work we discuss the impact of the new ICT techno-economic paradigm upon the vertical and horizontal boundaries of the firm and ask whether the change in the sources of competitive advantage has resulted in changes in the size distribution of firms and also in the degree of concentration of industries. Drawing both on firm-level and national statistical data we assess the evolution of the overall balances between the activities which are integrated within organizations and those which occur through market interactions. While the new paradigm entails revolutionary changes in the domain of technology, the modification in industrial structures has been somewhat more incremental. Certainly, the vertical and horizontal boundaries of firms have changed and together one is observing a turnover in the club of biggest world firms accounting also for a shift in the relative importance of industrial sectors. Nonetheless, we do not observe any abrupt fading away of the Chandlerian multidivisional corporation in favour of smaller less-integrated firms.
Keywords: 330; New techno-economic paradigm; Organizational change; Vertical integration; Boundaries of the firm; Visible hand; Technischer Fortschritt; Strukturwandel; Organisatorischer Wandel; Unternehmenserfolg; Vertikale Integration; Industrieökonomik